Strategies of Islamic Religious Education Teachers in Managing Administrative Burden to Sustain Teaching Effectiveness - Widyaningsih, Erna; Nashir, Muhammad Jafar (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This study aims to describe the various administrative burdens faced by Islamic Religious Education teachers and the strategic efforts taken to maintain the effectiveness of the learning process. This study employed a qualitative approach, utilizing a case study method, with five Islamic Religious Education teachers at the elementary school level in Karangpandan District as the research subjects. Data collection was conducted through in-depth interviews, field observations, and documentation reviews over a period of three months. Data were then analyzed through data reduction, data presentation, and conclusion drawing. The research is conceptually grounded in the theories of teacher professionalism and workload management, which provide a framework for understanding how teachers adapt to administrative pressures while maintaining instructional quality. The findings indicate that Islamic Religious Education teachers experience a variety of administrative pressures, including developing teaching materials, completing various administrative systems and performance reports, managing school documents, and carrying out additional administrative tasks. This burden has the potential to divert teachers' attention away from developing creative and innovative learning. Nevertheless, Islamic Religious Education teachers implement adaptive strategies such as efficient time management, utilizing digital technology, collaborating with colleagues, and simplifying administrative activities in accordance with school policies. These adaptive strategies help teachers maintain the quality of their teaching while fulfilling their primary function as educators and character builders of students.